Regulatory T cell-mediated anti-inflammatory effects promote successful tissue repair in both indirect and direct manners - Lei, Hong; Schmidt-Bleek, Katharina; Dienelt, Anke; Reinke, Petra; Volk, Hans-Dieter (Frontiers in Pharmacology, 2015)
Regulatory T cells (Tregs) offer new immunotherapeutic options to control undesired immune reactions, such as those in transplant rejection and autoimmunity. In addition, tissue repair and regeneration depend on a multitude of tightly regulated immune and non-immune cells and signaling molecules. There is mounting evidence that adequate innate responses, and even more importantly balanced adaptive immune responses, are key players in the tissue repair and regeneration processes, even in absence of any immune-related disease or infection. Thus, the anti-inflammatory and anti-apoptotic capacities of Treg can affect not only the effector immune response, creating the appropriate immune environment for successful tissue repair and regeneration, but growing evidence shows that they also have direct effects on tissue cell functions. Here we summarize the present views on how Treg might support tissue regeneration by direct control of undesired immune reactivity and also by direct interaction with non-immune tissue cells. We describe tissue-resident Treg and their specific phenotypes in skin, visceral adipose tissue, and skeletal muscle. In addition, we touch on the topic of osteoimmunology, discussing the direct interactions of Treg with bone-forming cells, such as osteoblasts and their mesenchymal stromal cell (MSC) progenitors—a field which is under-investigated. We hypothesize a cross-talk between Treg and bone-forming cells through the CD39–CD73-(adenosine)-adenosine receptor pathway, which might also potentiate the differentiation of MSCs, thus facilitating bone regeneration. This hypothesis may provide a road map for further investigations on the cross-talk between the immune and the skeletal system, and also enable the development of better strategies to promote bone repair and regeneration.